Induction of glioma stem cells by interleukin-1beta and transforming growth factor-beta - Liu, Ziyan (Kansas State University, 2011)
Transforming growth factor beta (TGF-β) and interleukin-1β (IL-1β) are both up-regulated in high grade gliomas and their elevated activities have been associated with prognosis in glioma patients. It is known that TGF-β is involved in proliferation and maintenance of glioma stem cells. In this study, I evaluated whether IL-1β also plays an important role in glioma stem cell development. Glioma stem cells are usually identified by using a sphere assay where glioma stem cells proliferate as neurospheres in serum free medium (SFM) in the presence of two growth factors: EGF and bFGF. However, LN229, a human glioblastoma cell line does not form neurospheres in SFM, suggesting that LN229 cells contain very few stem cells. I found that combination of IL-1β and TGF-β, but not IL-1β or TGF-β alone induced LN229 cells to grow as neurospheres in SFM. Furthermore, quantitative RT-PCR analyses show that the expression of stem cell markers (Nestin, Bmi1, Notch2, and LIF), cytokines (IL-1β, IL-6 and IL-8) and invasive genes (SIP1, β-integrin and N-Cadherin) are significantly enhanced in IL-1β /TGF-β induced spheres compared to the control. Using an invasion assay, drug resistance test, and colony assay, I found that LN229 sphere cells induced by IL-1β and TGF-β are more invasive, have increased drug resistant ability, and are more oncogenic in comparison to the control. Together, these results suggest that IL-1β cooperates with TGF-β to induce glioma stem-like cell phenotype.
Keywords: stem; interleukin 1 beta; Biochemistry (0487)